Sosialisasi Pencegahan Kekerasan Seksual terhadap Anak dan Remaja: Socialization of Prevention of Sexual Violence against Children and Adolescents - Andia, Novita; Putri, Noviyati Rahardjo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Sexual violence against children and adolescents is one of the serious problems faced by communities in various parts of the world. Based on real-time data from the Ministry of Women's Empowerment and Child Protection starting from January 1 to 31, 2025, data on cases of sexual harassment and violence in the 12-24 age group in the female category occupied the largest percentage, namely 41.8. The form of this community service activity is education on the Prevention of Sexual Violence Against Children and Adolescents which was carried out on Monday, August 5, 2024, at 19.30-21.00 WIB, in Jembrak Village, Pabelan District, Semarang Regency. The target partners are adolescents aged 10-20 years as many as 30 adolescents. Evaluation of the success of the activity is shown by an increase in adolescent knowledge scores before and after the implementation of education from 24.6 to 29.4. The suggestion for implementing the next community service activity is an educational activity that involves a wider community outside the Posyandu Remaja health cadres so that it is hoped that the scope of community life is a safe means for adolescents to grow and develop optimally.